The Role of Brand Image, Product Quality and Price in Improving Product Purchasing Decisions - Muhammad Edo Fiorentino; Maheni Ika Sari; Tatit Diansari Reskiputri; Nurul Qomariah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine the effect of brand image, product quality and price on purchasing decisions for tofu products at Tamanan Bondowoso). The population is all people who buy tofu products at Tamanan Bondowoso. The number of samples was determined as many as 90 respondents with non-probability sampling technique and purposive sampling method. To test the measuring tool in the form of a research questionnaire, the validity test tool and data reliability test tool are used. Multiple linear regression analysis, F test and t test were used to test the research hypothesis. The test results show that there is a significant influence between brand image and purchasing decisions with a significance level of 0.013 (<0.05). The second result shows that there is a significant influence between product quality and purchasing decisions with a significance level of 0.002 (p <0.05). The third result shows that there is a significant effect between price and purchase decision with a significance level of 0.002 (p <0.05). Thus it can be concluded that the independent variables consisting of brand image, product quality and price together have an effect on the dependent variable (Y) purchasing decisions.